TWO APPROACHES TO THE PROBLEM OF EVIL - R K Tripathi (Journal of Dharma, 2020)
There seem to be two basic approaches to the problem of evil. This is because the problem is formulated in two basically different ways. One way of formulating the problem is: What is the place of evil in a world created by God who is all might, all wisdom and all goodness? This is what may be called the religious approach or the approach presupposing God as the creator of the universe. It is as if the problem has arisen just because of the acceptance of the existence of God as creator and it would not have arisen otherwise.